Are there correlations between radiographic grade levels and modified grade levels of periodontitis? - Fatih Karaaslan; Ahu Dikilitaş; Esra Özge Aydın; Vesile Şen; Şerife Esra Kurt (Wolters Kluwer Medknow Publications, 2021)
Background: At the 2017 World Workshop on the Classification of Periodontal and Peri-Implant Diseases and Conditions, periodontitis was reclassified according to a multidimensional staging and grading system. Grading takes variabilities in the rate of disease progression into account, relying on recognized progression risk factors, and is based on the assessment of bone loss at the worst-affected tooth in the dentition as a function of age, which is then modified by factors such as smoking and diabetes mellitus. In this context, the aim of this study was to determine whether there are correlations between radiographically calculated grades and grades modified by the presence of smoking or diabetes. Materials and Methods: In this descriptive study, individuals diagnosed with periodontitis according to the 2017 classifications were examined. The grade of periodontitis was measured using periapical radiography. A modified-grade level was assigned to the patients according to their glycated hemoglobin levels (in diabetics) or their smoking status. Results: The study included 341 individuals. No statistically significant relationship was revealed by Chi-square testing (P > 0.05) or in the kappa agreement index between the modified grades and the radiographic grades. Conclusions: Although there was no correlation between radiographic grade and modified grade in smokers and diabetic individuals, increasing the grade score in these individuals in accordance with the 2017 classification provides clinicians the opportunity to develop a risk-based treatment plan, commensurate with the severity of periodontal disease and the level of risk.